Index to Records of ante-bellum Southern plantations locations, plantations, surnames and collections - Cooper, Jean L. (McFarland & Co., 2009)
"Designed for both professional and amateur genealogists and other researchers, this index provides a detailed guide to materials available in the extensive Records of Ante-Bellum Southern Plantations microfilm set. The items indexed include deeds, wills, estate papers, genealogies, personal and business correspondence, account books, slave lists, and many other types of records"--Provided by publisher.